OPTIMIZATION OF WORKFORCE ASSIGNMENT USING THE HUNGARIAN METHOD BASED ON POM-QM IN A BARBERSHOP BUSINESS - Rumetna, Matheus Supriyanto; Lina, Tirsa Ninia; Narahawarin, Adrian P.; Bara, Iluminata; Maindoka, Citra P. (Journal of Computer Science and Technology (JCS-TECH), 2026)
This study discusses Skill Daeng, a barbershop business established on April 9, 2018, located at Km.9 next to the PLTD, Malaingkedi Village, Malaimsimsa District, Sorong City, Southwest Papua. Skill Daeng offers three main services: barbershop, perming, and smoothing, run by two workers, Nanang and Baim. In one week, the profit from the barbershop service obtained is IDR 2,125,000 for Nanang and IDR 1,370,000 for Baim. In addition, both workers also earn additional income from perming services of IDR 200,000 and smoothing of IDR 140,000. However, the current division of tasks is not optimal, which causes an imbalance in the utilization of each individual’s skills and the profits obtained by each worker. The purpose of this study is to maximize profits based on task allocation according to worker abilities. This study uses the Hungarian method to solve the assignment problem by adding one dummy employee to equalize the number of workers and jobs. By creating a profit table and applying the steps of the Hungarian method, both manually and using the POM-QM for Windows V5 application, optimal assignment results were obtained with a total profit achieved in a week of IDR 2,325,000. These results indicate that efficient assignment management can increase profits and provide a fairer distribution of work.